Isolasi Bakteri Fiksasi Nitrogen dan Fosfat pada Limbah Cair Karet (Hevea brasiliensis) - Sartika Kumala Dalimunthe; Kartika Manalu (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This research was conducted with the aim of knowing the types of bacteria that are able to fix nitrogen and dissolve phosphate in liquid rubber waste in Perdamean Village, Labuhanbatu Regency. The research method used is the description method with bacterial isolation techniques, and then tests are carried out, namely testing the ability of nitrogen fixation and testing the ability of phosphate solubilizers. The results showed that bacterial isolates capable of fixing nitrogen were found to have high absorbance values, namely 1,340 ABS. In the phosphate solubilizing ability test, there were 2 isolates that were unable to dissolve phosphate. In conclusion, isolating nitrogen and phosphate fixation bacteria from liquid rubber waste is a way to prevent pollution and the destruction of existing ecosystems in the environment. Keywords: Nitrogen Fixation, Rubber Liquid Waste, Phosphate Solvent